Materials challenges in high-energy batteries enabling ultra-fast charging and non-flammable performance for electric vehicles - Lee, Hyojoo; Suh, Joo Hyeong; Chaudhary, Rashma; Mun, Junyoung; Kim, Jung Ho (Frontiers in Batteries and Electrochemistry, 2025)
Development of advanced battery technologies for electric vehicles (EVs) has primarily focused on achieving high energy density, non-flammability, and fast charging capability. While commercial batteries have served as the backbone for EVs, numerous material challenges still remain to achieve these desired advancements. This perspective presents an overview of state-of-the-art strategies and recent breakthroughs aimed at overcoming the limitations of next-generation EV batteries.